ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM PEMBELIAN MALANG STRUDEL (Studi Pada Pelanggan Malang Strudel, Batu) - Rizki Ahmad Subekti; Sri Hindarti; Zainul Arifin (Program Studi Agribisnis, 2020)
This study aims to identify the characteristics of consumers and analyze the factors that influence consumer decisions in purchasing Malang Strudel. The data used are primary data from observations and interviews conducted in December 2019 located in Malang Strudel Batu with a sample of 30 respondent consumers. Data analysis techniques used descriptive analysis and logit model regression analysis. The results showed that the majority of consumers were 77% women, judging from the educational background of Malang Strudel consumers, the average was in the highly educated category of 70% undergraduate to post graduate 23%. Judging from the monthly income, most Malang Strudel consumers are employed and have a high income from yaituRp. 5,000,000 60% per month and ≥ Rp. 5,000,000 with 40%. Factors that influence consumer decisions are price, taste, and durability with α = 0.1Keywords: strudel, consumers, consumer decisions